Melatonin as a Novel Interventional Candidate for Fragile X Syndrome with Autism Spectrum Disorder in Humans - Won, Jinyoung (Int J Mol Sci, 2017)
Fragile X syndrome (FXS) is the most common monogenic form of autism spectrum disorder (ASD). FXS with ASD results from the loss of fragile X mental retardation (fmr) gene products, including fragile X mental retardation protein (FMRP), which triggers a variety of physiological and behavioral abnormalities. This disorder is also correlated with clock components underlying behavioral circadian rhythms and, thus, a mutation of the fmr gene can result in disturbed sleep patterns and altered circadian rhythms. As a result, FXS with ASD individuals may experience dysregulation of melatonin synthesis and alterations in melatonin-dependent signaling pathways that can impair vigilance, learning, and memory abilities, and may be linked to autistic behaviors such as abnormal anxiety responses. Although a wide variety of possible causes, symptoms, and clinical features of ASD have been studied, the correlation between altered circadian rhythms and FXS with ASD has yet to be extensively investigated. Recent studies have highlighted the impact of melatonin on the nervous, immune, and metabolic systems and, even though the utilization of melatonin for sleep dysfunctions in ASD has been considered in clinical research, future studies should investigate its neuroprotective role during the developmental period in individuals with ASD. Thus, the present review focuses on the regulatory circuits involved in the dysregulation of melatonin and disruptions in the circadian system in individuals with FXS with ASD. Additionally, the neuroprotective effects of melatonin intervention therapies, including improvements in neuroplasticity and physical capabilities, are discussed and the molecular mechanisms underlying this disorder are reviewed. The authors suggest that melatonin may be a useful treatment for FXS with ASD in terms of alleviating the adverse effects of variations in the circadian rhythm.